Thermal and physical properties of CNF/glutaraldehyde-gelatin-based hydrogel - ROSLIANA LUBIS; SRI WAHYUNA SARAGIH; WARDATUL HUSNA IRHAM; AJMAIN AJMAIN; SAISA SAISA (Universitas Syiah Kuala, 2023)
The use of hydrogel as a wound dressing material is currently being massively developed. In addition to functioning to protect wounds, the use of hydrogel can also provide moisture in a measured manner and can be used as a drug delivery medium. In this study, hydrogel based on CNF and glutaraldehyde crosslinking agent and addition of gelatin were developed with various compositions 0.25; 0.5; 0.75 g to increase the ability of CNF and hydrogel to absorb water so that it is good to be applied as a wound dressing. The composting of the three materials aims to obtain a hydrogel with good thermal and physical properties. Based on physical character for a good ratio of swelling (666,62%) and degree of cross-linking (94%) on the hydrogel with a composition variation of 0.5 g of CNF addition. For the thermal stability of hydrogel var 2, TMax 591oC provides better thermal stability than var 1 and var 3. The morphology of hydrogel shows very small and evenly distributed pores on the surface which can absorb more water.